The Black feminist spatial imagination and an intersectional environmental justice - Ducre, Kishi Animashaun (Environmental Sociology, 2018)
Starting with seminal work from Katherine McKittrick and Katherine McKittrick and the late Clyde Woods, this paper compares and contrasts articulations of justice as espoused by Black feminism, ecofeminism, and the movement for environmental justice. The utilization of an intersectional genealogical approach allows for examination of the ways in which these movements might serve as the ideological bases for a Black feminist spatial imagination and an intersectional environmental justice. A Black feminist spatial imagination is an orientation that accounts for the merger of frames around race, gender, and ecology; it serves as a unique departure from conventional Black feminist analysis by its particular attention to the construct of space in Black feminist epistemology. Analysis reveals that manifestos engage similar strategies around boundedness, an identification among a collective identity and the subject of reproductive justice and liberation as wresting control and self-determination of physical bodies. The final task is an outline of essential tenets for a singular notion of justice of a Black feminist spatial imagination which incorporates the spirit of all of three manifestos and expands current environmental justice discourse to include those ‘who know no one knows’ while highlighting Black women’s agency in environmentally degraded environments. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: afro-féminisme; amériques; approches et analyses; corps; environnement; féminismes noirs; intersectionnalité; justice environnementale; justice reproductive; projet charge mentale; régions géographiques; thématiques; écoféminisme; états-unis

Libère-toi Cyborg! : le pouvoir transformateur de la science-fiction féministe - Larue, Ïan (Éditions Cambourakis, 2018)
Gynoïdes, sorcières, vampires, chiennes et souris de laboratoire : toutes sont liées à la cyborg de Donna Haraway. Reprenant la liste d'auteurs et autrices de science-fiction féministe citées à la fin du Manifeste cyborg, Ïan Larue redéfinit cette figure fondatrice dans la pensée de la philosophe :"La cyborg, c'est l'esclave noire qui apprend à lire dans un roman d'Octavia Butler ; la jeune fille encapsulée qui, loin de se sentir handicapée, connaît des milliers de connexions ; la fille-orque transportée dans les étoiles. La cyborg est l'hybride suprême, hybride entre une femme réelle et un personnage de roman qui se superpose à elle pour la doter de mille nouvelles possibilités dont celle, fondamentale, de faire éclater capitalisme, famille et patriarcat."
Keywords: approches et analyses; arts; corps; cours; discipline; fem3600; patriarcat; premier cycle; systèmes d'oppressions; thématiques; écoféminisme; études littéraires